Bibliometric Analysis on the Impact of Electronic Medical Records Implementation on Prescribing Errors: Trends and Research Gaps - Karla Rochyana Heliati; Elsye Maria Rosa; Kusbaryanto Kusbaryanto (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: Patient safety is a crucial issue worldwide, with medication errors particularly prescribing errors posing significant risks to clinical outcomes. Electronic Medical Records (EMR) have been widely implemented to minimize these errors. However, the scope and evolution of EMR’s impact on prescribing errors need a comprehensive analysis.Objective: This study systematically reviews the research landscape on the relationship between EMR implementation and prescribing errors using bibliometric analysis to identify key trends, research clusters, and future research opportunities.Methods: A qualitative bibliometric analysis was conducted on 117 articles published between 2020 and 2024, retrieved from the Scopus database. The PRISMA framework guided the screening process, including title, abstract, and full-text reviews based on predefined inclusion criteria. VOSviewer software was employed to visualize co-occurrence networks, overlay maps, and density distributions to identify dominant research themes.Results: Three primary cluster emerged: (1) technological innovations to detect and prevent prescribing errors in hospital environments; (2) integration of clinical practice with digital tools to improve healthcare quality; and (3) Optimization of EMR accuracy and clinical decision support systems to enhance efficiency and safety. Despite increasing research output, gaps persist regarding the long-term effects of EMR interventions, user acceptance, the synergy between technology and staff training, and interdisciplinary collaboration in EMR development.Conclusion: This bibliometric study synthesizes current knowledge and reveals critical research gaps. Strengthening user centered and interdisciplinary approaches is essential to further reduce prescribing errors and improve patient safety.